Performance evaluation of SCM-WDM microcellular communication system in the presence of XPM - Subramaniam, Shamini; Abbou, F. M.; Chuah, Hean Teik; Dambul, Katrina D. (The Institute of Electronics, Information and Communication Engineers, 2005)
The crosstalk effects in a subcarrier multiplexed-wavelength division multiplexed (SCM-WDM) system due to cross phase modulation (XPM) have been investigated. The variation of XPM induced distortion is investigated for parameters such as transmission distance, frequency and channel spacing. Results show that the XPM induced dispersion in an SCM-WDM system is directly proportional to the transmission distance and frequency and inversely proportional to the channel spacing.